Exploration of Students Perception Towards Game-Based Biomechanics Learning: A Qualitative Study - Sinaga, Ade Maruba; Waruwu, Andreas Martin Saputra; Lumbantoruan, Domu Firman Syah; Siburian, Esra Olivia; Pakpahan, Kelvin Padrevio; Siahaan, Samuel Febrianto; Mahmuddin, Mahmuddin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore students’ perceptions of game-based learning in biomechanics. The research is grounded in the need for innovative learning methods that can enhance engagement, motivation, and comprehension of biomechanical concepts, which are often considered complex and abstract. The study employed a qualitative exploratory design, with data collected through the analysis of scientific articles and relevant research published within the last five years. The findings indicate that game-based learning fosters more interactive and enjoyable learning experiences, encouraging students to actively engage with biomechanical concepts. Students reported an increase in intrinsic motivation, deeper conceptual understanding, and the development of critical thinking skills. Nevertheless, several challenges were identified, such as limited facilities, teachers’ readiness in designing educational games, and variations in students’ learning styles. Overall, this study highlights that integrating games into biomechanics learning holds significant potential to improve learning effectiveness, provided that adequate facilities, teacher training, and proper implementation strategies are ensured.